PENGARUH PEMBERIAN BUBUR KACANG HIJAU DAN SUSU BUBUK TERHADAP STATUS GIZI ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA KECAMATAN SUNGAI APIT KABUPATEN SIAK - Yunita, Lilis Yunita Lilis; Novianti, Ria Novianti Ria; ', Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research aims to understand the influence of the provision of green bean porridge and milk powder about the status of child nutrition age 5-6 years in kindergarten coaching land kecamatan sungai apit siak district. Population sizes in this research some 76 children and sample in this research was 26 children. Technique data collection in use the observation. Technique analysis the data in use in this research was analysis uji-t. The research that has been done, it can be in some attraction conclusion which as follows: 1). After in give treatment the provision of green bean porridge and milk powder, the average children healthy increased to 83 % which means the provision of green bean porridge and milk powder successfully salubrious children. 2). Through skills treatment the provision of green bean porridge and milk powder, the average healthy child rose to 77 % which means the granting of green bean porridge and milk powder managed to improve liveliness children as much as 29 % . 3).Once treated giving green bean porridge and milk powder,the average activity of children increased to 77%.which means giving the green bean porridge and milk powder managed to increase activationof children about 29%. Good Nutritionis important for children, because it helps the development of children in the future.Keywords: green bean porridge and milk powder , nutrition status